Analysis of the Number of Intercity Passengers Via Trans Java Island for the Period 2023-2024 at the DAMRI Bus Terminal - Prasetyo; Aprilia Dwi Aisyah; Lasron Saputra Lumbanraja; Rovia Ramadhani; Erni Putri Setia Zendrato; Silvi yani; Ellin Marlina; Rafli Pahlevi; Miftakul Huda (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines ticket sales trends during the 2024 Lebaran Transportation period at DAMRI Bus Terminals, focusing on various intercity routes. DAMRI, a leading public transportation company in Indonesia, prioritizes performance, quality, and passenger safety in its services. Data analysis reveals significant ticket sales across routes such as Surabaya-Malang, Lampung, and Pontianak, indicating passenger preferences during peak travel seasons. The results of this study provide valuable insights to optimize intercity transportation services and meet passenger demand effectively